1970
DOI: 10.1128/aem.20.5.825-833.1970
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Human Melioidosis with Indirect Hemagglutination and Complement Fixation Tests

Abstract: An indirect hemagglutination (IHA) test and a complement fixation (CF) test were evaluated from test results on sera from 212 human melioidosis patients of which 119 were culturally proved cases. Significant antibody titers (IHA titers of 1:40 or greater and CF titers of 1:4 or greater) were demonstrated with either test in all except five patients. IHA and CF titers ranged as high as 1:20,480 and 1:1,024, respectively. Antibodies were usually demonstrated by both tests 1 week after onset of disease. Transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 8 publications
(9 reference statements)
1
52
0
Order By: Relevance
“…We prepared antigens in accordance with published methods, unless otherwise stated (17,18). For IHA, we used crude culture filtrate antigens from pooled isolates with the following specifications: B. pseudomallei Thai clinical isolates 199a and 207a (19), B. thailandensis Thai environmental isolates E264 (ATCC700388) and STBCC006 (20), and BTCV Thai environmental E555 and USA clinical isolate CDC3015869.…”
Section: Antigen Preparationmentioning
confidence: 99%
“…We prepared antigens in accordance with published methods, unless otherwise stated (17,18). For IHA, we used crude culture filtrate antigens from pooled isolates with the following specifications: B. pseudomallei Thai clinical isolates 199a and 207a (19), B. thailandensis Thai environmental isolates E264 (ATCC700388) and STBCC006 (20), and BTCV Thai environmental E555 and USA clinical isolate CDC3015869.…”
Section: Antigen Preparationmentioning
confidence: 99%
“…Furthermore, Nigg and Johnson (11) reported that P. aeruginosa antigen was shown to be capable of cross-reacting with antibodies to P. pseudomallei surface antigens when complement-fixation serologic technique was used. Similarly, cross-reactivity between antigens of P. pseudomallei and P. stutzeri was also evident when complement-fixation procedure was employed by Alexander et al (1). Exotoxins of P. pseudomallei are proteins of relatively lower molecular weight (36,000 daltons) compared to that of P. aeruginosa exotoxin (M.W.…”
mentioning
confidence: 92%
“…In the present study, we are able to demonstrate the usefulness of polysaccharide microarray technology for the detection of serum antibodies against B. mallei and B. pseudomallei. An indirect hemagglutination and a complement fixation (CF) test had been the routine procedure for the serologic diagnosis of human melioidosis caused by B. pseudomallei infection (Alexander et al, 1970;Wuthiekanum et al, 2006). B. mallei infections (glanders) in horses had been serologically diagnosed employing CF test (Marek and Manninger, 1945).…”
Section: Polysaccharide Microarraymentioning
confidence: 99%